Targeting the IL34-CSF1R axis improves metastatic renal cell carcinoma therapy outcome via immune-vascular crosstalk regulation - Andrea Emanuelli; Wilfried Souleyreau; Tiffanie Chouleur; Bram Boeckx; Yasmine Pobiedonoscew; Lindsay Cooley; Marie-Alix Derieppe; Julie Martineau; Damien Ambrosetti; Jean-Christophe Bernhard; Catherine M. Sawai; Diether Lambrechts; et al. (iScience)
Summary: Current therapies ultimately fail to eradicate metastatic renal cell carcinoma (RCC). Validated biomarkers and a better understanding of the mechanisms causing therapy resistance are still needed. Here we demonstrate that interleukin-34 (IL34) is associated with poor prognosis, metastasis, and therapy resistance in RCC. In mice, single-nucleus RNA sequencing and phenotyping reveal that the IL34-enriched tumor microenvironment displays immunosuppression and nonfunctional vasculature, two key features of therapy resistance. Mechanistically, IL34 increases migration of monocyte-derived tumor-associated macrophages (MD-TAMs) in primary tumors and lung metastases through colony-stimulating factor 1 receptor (CSF1R). Blockade of CSF1R by the Food and Drug Administration-approved drug pexidartinib contrasts MD-TAMs accumulation observed in the IL34-enriched microenvironment and improves response to sunitinib or anti-PD1 treatment to reduce metastatic growth. Altogether, our data highlight the role of the IL34-CSF1R axis in regulating the tumor immune-vascular crosstalk in RCC and indicate pexidartinib as a therapeutic alternative in combination with current therapies.